Dissolution behavior and chemical characteristics of low molecular weight compounds from tectonically deformed coal under tetrahydrofuran extraction. (1st December 2019) - Zhang, Shuo; Zhang, Xiaodong; Hao, Zongchao; Wang, Zhiming; Lin, Junfeng; Liu, Mingren
Abstract: Tectonically deformed coal (TDC) is formed by complex and variable tectonic stresses. The induced physical-chemical effects result in a variety of chemical compositions and structures in TDCs. In this work, medium volatile bituminous coals with four types of tectonic deformation were selected and extracted with tetrahydrofuran to investigate the dissolution behavior and distribution of low molecular weight compounds in TDCs. The results revealed that a higher degree of tectonic deformation in the coal produces a higher total extraction yield as the total extraction time increases. A diffusion model also establishes a good relationship between the extraction mass and extraction time, and the diffusion coefficient Dobs can be used to describe the extraction kinetics. Chemical analysis of the extracts using column chromatography and GC/MS further found that there are more binding points for forming non-covalent bonds in long chain aliphatic hydrocarbons. So the alkanes with more than 20 carbon atoms are often dissolved at the medium and late stages. Aromatic compounds, which are mostly dissolved at the medium stage, are essentially combined into the coal macromolecular structure by π–π stacking interactions or hydrogen bonds. While a large number of heteroatomic compounds are distributed widely in coals, resulting in diverse dissolution behaviors. Under the tectonic stresses, the type and content of low molecular weight compounds in TDCs increase compared to intact coal. Particularly, an increase in tectonic deformation appeared to produce more aromatic hydrocarbons and long chain alkanes in TDCs, whilst the presence of heteroatomic compounds becomes more complex.